Pharmacological Targeting of Endoplasmic Reticulum Stress in Pancreatic Beta Cells. (February 2021) - Bilekova, Sara; Sachs, Stephan; Lickert, Heiko
Abstract : Diabetes is a disease with pandemic dimensions and no pharmacological treatment prevents disease progression. Dedifferentiation has been proposed to be a driver of beta-cell dysfunction in both type 1 and type 2 diabetes. Regenerative therapies aim to re-establish function in dysfunctional or dedifferentiated beta cells and restore the defective insulin secretion. Unsustainable levels of insulin production, with increased demand at disease onset, strain the beta-cell secretory machinery, leading to endoplasmic reticulum (ER) stress. Unresolved chronic ER stress is a major contributor to beta-cell loss of function and identity. Restoring ER homeostasis, enhancing ER-associated degradation of misfolded protein, and boosting chaperoning activity, are emerging therapeutic approaches for diabetes treatment. Highlights: Beta-cell dysfunction and dedifferentiation precedes T1D and T2D onset and offers a window of opportunity for early pharmacological intervention. Chronic ER stress is the main contributor to beta-cell dysfunction, which can lead to beta-cell apoptosis and diabetes. Small molecules that balance ER homeostasis by targeting UPR mediators, ERAD, and aiding protein folding promise efficacy for the treatment of T1D and T2D.